Electrically modulating and switching infrared absorption of monolayer graphene in metamaterials. (June 2020) - Chen, Jing; Chen, Siyu; Gu, Ping; Yan, Zhendong; Tang, Chaojun; Xu, Zhijun; Liu, Bo; Liu, Zhengqi
Abstract: Electrically modulating and switching the light absorption properties of monolayer graphene in near-infrared region has potentials in optoelectronic devices (e.g., photodetectors) and optical communication systems (e.g., modulators). In this work, we demonstrate numerically a broadband near-infrared absorption enhancement of monolayer graphene, due to the magnetic dipole resonance in metamaterials. The broadband light absorption in monolayer graphene can be largely modulated to realize an electrically switchable effect, via bias voltage for the interband transition of graphene to be near the magnetic dipole resonance. The absorption modulation depth is able to vary quickly from almost zero to nearly 100% in a very narrow wavelength range around the interband transition. Graphical abstract: Electrically modulating and switching the light absorption properties of monolayer graphene in near-infrared region has potentials in optoelectronic devices (e.g., photodetectors) and optical communication systems (e.g., modulators). In this work, we firstly demonstrate numerically a broadband near-infrared absorption enhancement of monolayer graphene, due to the magnetic dipole resonance in metamaterials. Then, we show that the broadband light absorption in monolayer graphene can be largely modulated to realize an electrically switchable effect, via bias voltage for the interband transition of graphene to be near the magnetic dipole resonance. The absorption modulation depth is able to vary quickly from almost zero to nearly 100% in a very narrow wavelength range around the interband transition. Image 107